2021
DOI: 10.3389/fcell.2021.655152
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast (CAF) Heterogeneity and Targeting Therapy of CAFs in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal disease that typically features a dramatic desmoplastic reaction, especially fibroblasts. The roles of cancer-associated fibroblasts (CAFs) in PDAC have received more attention in recent years. As increasing evidence suggests the heterogeneity of CAFs in PDAC, different CAF subtypes have been shown to support tumor growth, while others suppress cancer proliferation. Myofibrotic CAFs (myCAFs) show alpha-smooth muscle actin (α-SMA)high interleukin-6 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 107 publications
5
86
0
Order By: Relevance
“…These data show that collagen deposition in the PDAC SiaJ model resembles what has earlier been described in the literature in in vitro models [61]. TGF-ß has also been shown to be part of the PF to CAF transition [36]. Since the PFs resemble the CAF type III collagen production after stimulation by TGF-ß1, it could be interesting to investigate if the PFs achieved a more CAF-like or myofibroblast phenotype.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These data show that collagen deposition in the PDAC SiaJ model resembles what has earlier been described in the literature in in vitro models [61]. TGF-ß has also been shown to be part of the PF to CAF transition [36]. Since the PFs resemble the CAF type III collagen production after stimulation by TGF-ß1, it could be interesting to investigate if the PFs achieved a more CAF-like or myofibroblast phenotype.…”
Section: Discussionsupporting
confidence: 79%
“…They have been directly linked to tumorigenesis, by being involved in cell proliferation, migration, invasion and metastasis, inflammation, and drug resistance [35]. As the amount and activity of CAFs and tumor fibrosis have been shown to be prognostic for survival in many types of cancer, several clinical trials are exploring drugs targeting CAFs, either directly, or by targeting downstream CAF signaling, such as anti-stromal therapies [36]. While CAFs and tumor fibrosis have promising potential as novel targets there are also challenges associated with this approach [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3A-B, Mindin differentially primes Sca1+ fibroblast to an inflammatory phenotype, which is consistent with iCAFs 25 . In a similar vein, treatment of Mindin can endow CD26+ fibroblasts to become more contractile and secrete elevated collagen (Figure 4B and F), which is consistent with a myCAF phenotype 25 . Furthermore, it has been shown that CD10, C5a, and GPR77 are signatures of a subset of CAFs in breast and lung cancer patients 51 .…”
Section: Resultssupporting
confidence: 81%
“…The MHCs, HLA-DOA, HLA-DPA1, and HLA-DPB1, positively associated with LOXL3 all belongs to MHC Class II molecules (104). MHC class II molecules were found to be expressed by antigen-presenting cells, including antigenpresenting cancer-associated fibroblasts (apCAFs) (105,106). Therefore, these positive association of the MHC Class II molecules might be indirect evidence of apCAFs in HCC, and drugs targeted on these apCAFs might have potential therapeutic values and future studies are needed for further clarification.…”
Section: Discussionmentioning
confidence: 99%